The predictive power of CD3+ T cell infiltration of oral squamous cell tumors is limited to non-diabetic patients. (28th February 2021) - Spanier, Gerrit; Ugele, Ines; Nieberle, Felix; Symeou, Luisa; Schmidhofer, Sandra; Brand, Almut; Meier, Johannes; Spoerl, Steffen; Krupar, Rosemarie; Rümmele, Petra; Siska, Peter; Renner, Kathrin; et al.
Abstract: Diabetes mellitus type II (DM) and immune cell infiltration determine patient outcome in many tumor entities. Here we studied a possible link between the metabolic and immune cell status of OSCC patients. Glucose transporter (GLUT) 1 mRNA expression was elevated in all tumor samples, whereas other glycolytic markers such as lactate dehydrogenase (LDH) A or monocarboxylate transporter (MCT) 1 were increased in tumor samples from patients with diabetes and these patients had a significantly worse prognosis compared to non-diabetic patients. Analyses of immune cell infiltration in tumors from diabetic and non-diabetic patients revealed an increased leukocyte (CD45 + ) infiltration compared to normal mucosa only in non-diabetic patients. In line, the amount of CD3 + T cells per mm 2 tumor tissue, was elevated in patients without diabetes and crucial for patient outcome in OSCC patients without diabetes, as compared to healthy mucosa using fluorescence immunohistochemistry in tissue microarrays of 229 patients. Our results demonstrate that diabetes is a prognostic factor for OSCC patients and associates with decreased leukocyte and CD3 + infiltration indicating that metabolic differences between diabetic and non-diabetic patients may alter tumor-infiltrating T cells and thereby determine patient outcome. Highlights: Diabetes mellitus type II (DM) is a significant predictor for overall survival in oral squamous cell carcinoma (OSCC). Intratumoral CD3 +  T cell infiltration is lower in diabetic OSCC patients. Positive prognostic impact of central CD3 +  T cells on survival could only be observed in non-diabetic OSCC patients.